Recognition, Identity, and Authenticity in the Blues - Koskinen, Heikki J. (Itinerari, 2023)
This paper analyses issues of recognition, identity, and authenticity in connection with blues music, blackness and whiteness. Using conceptualizations from recognition theory, the discussion begins by raising some fundamental problems encountered in the troubled cultural politics of the contemporary blues scene. The two positions of Black Blues Particularism and Blues Universalism are then distinguished, characterized, and critically discussed, while looking at some relevant examples from the literature. As its constructive contribution, the paper concludes by suggesting that musical ideas should be recognized in similar fashion to scholarly ones, that is, by respecting and crediting the original sources, while openly utilizing and freely developing them into further directions.